PENINGKATAN DAYA DUKUNG TANAH DENGAN METODE GROUTING : STUDI KASUS KALI SEMARANG, JAWA TENGAH - Rahadian Aksono (Program Studi Teknik Geologi, Fakultas Teknik, Universitas Diponegoro, 2013)
Kali Semarang in Semarang city will be constructed embankment. The result of soil investigation by sondir or cone penetration test (CPT) was obtained in the form of very soft clay to soft clay and has low soil bearing capacity. This may in turn damage the embankment which will be built because of a decline slowly building embankment. So it need the compaction soil by compaction grouting for increasing soil density and soil bearing capacity.The purpose of the research is to know the soil types and soil bearing capacity in areas of research by sondir / CPT data, determining the grouting implementation methods improving very soft soil forces, determining the soil type changes after grouting, and comparing the soil bearing capacity value before and after grouting.The method used in this research is the soil investigation by using the cone penetration test (CPT) or sondir. CPT before grouting has been done 3 points by Sondir-1, Sondir-2, and Sondir-3, while CPT after grouting has been done by Sondir-1. Afterwards, the CPT’s data was processed dan analysed by using the software of Corel Draw X4, Microsoft Exel 2007.The results of the processing and analysis of data is clay soil until depth of 20 meters. Very soft clay is in the depth of 14 meters and soft clay is in the depth of 20 meters. The soil types is very soft clay and soft clay.Therefore, it is necessary done compaction by compaction grouting. In term of increasing soil bearing capacity, grouting gave the effect of change in soil types at the grouting point in the depths of 14 meters to be sandy silt, 20 meters to be the silty sand, and 3,6-3,8 meters to be sandy silt. Soil bearing capacity at 30ty day after the grouting was around from 29,13–79,00 ton/m2 atau 2,91–7,9 kg/cm2 and the average sondir result was 49,10 ton/m2,whereas before the grouting result was around 20,10–28,00 or 2,01–2,8 kg/cm2and for the average result was 23,25 ton/m2.